2023
DOI: 10.2174/1566524022666220607163232
|View full text |Cite
|
Sign up to set email alerts
|

In Transfusion-Dependent Thalassemia Children, Increased Iron Overload is Associated with Lower Serum Alpha-Klotho, Which is Strongly Associated with Lower Total and Ionized Calcium Concentrations

Abstract: Background: Patients with transfusion-dependent thalassemia (TDT) show disorders in calcium metabolism. The α-Klotho protein is predominantly expressed in tissues that are involved in calcium homeostasis, and lowered levels are associated with bone disease. The aim of the study is to examine the associations between low α-Klotho status and calcium metabolism in relation to iron status in children with TDT. Methods: Calcium, α-Klotho, parathyroid hormone (PTH), calcyphosin, vitamin D3, phosphorous, fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…14,15 The study participants' mean age was 19.59±7.59 years, similar to Shawkat et al study, 16 while other studies reported a lower/higher mean age than this study. [17][18][19] Most of the patients in this study were females, which is consistent with the study conducted in Iran by Bordbar et al 20 but it is not agreed with another study conducted in Iraq. 21,22 Regarding the BMI, the results showed that the obtained mean within the normal range.…”
Section: Discussionsupporting
confidence: 73%
“…14,15 The study participants' mean age was 19.59±7.59 years, similar to Shawkat et al study, 16 while other studies reported a lower/higher mean age than this study. [17][18][19] Most of the patients in this study were females, which is consistent with the study conducted in Iran by Bordbar et al 20 but it is not agreed with another study conducted in Iraq. 21,22 Regarding the BMI, the results showed that the obtained mean within the normal range.…”
Section: Discussionsupporting
confidence: 73%
“… 26 A case–control study found that total and ionized calcium were inversely associated with iron overload in children with transfusion‐dependent thalassemia. 27 It is well known that iron overload is an important marker of ferroptosis. In conclusion, an imbalance in calcium homeostasis may be one of the most important causes of ferroptosis.…”
Section: Vitamin D and Ferroptosismentioning
confidence: 99%